Application of Social Research Learning Model in Overcoming Intolerance and Hate Speech on Social Media Among Students - Wayan Gastiadirrijal; Syahidin Syahidin (Lembaga Yasin AlSys, 2026)
Advances in social media have revolutionized communication but simultaneously fueled intolerance and hate speech among students, eroding empathy, tolerance, and digital ethics in diverse societies such as Indonesia. This library-based descriptive qualitative study examines the Social Inquiry Learning model developed by Massialas and Cox within Islamic Education (Pendidikan Agama Islam/PAI) as a pedagogical response to these challenges. Primary data from credible books, journals, and empirical studies were systematically reviewed and analyzed through data reduction, thematic presentation, and conceptual synthesis, with validity ensured via triangulation of sources. The findings reveal that the model’s structured stages—problem identification, hypothesis formulation, data collection, moral analysis, and action—cultivate critical thinking, moral intelligence, and tolerance by integrating scientific inquiry with Islamic values such as rahmatan lil alamin and tasamuh. When applied through case studies and project-based learning in “reflection classrooms,” the model enhances students’ analytical skills, religious moderation, and ethical digital citizenship and performs more effectively than conventional instructional methods. At the same time, its implementation faces constraints related to limited instructional time and gaps in teacher competence, which can be addressed through targeted professional development and digital literacy initiatives. Overall, the Social Inquiry Learning model offers a transformative PAI pedagogy that bridges theory and practice to foster resilient, tolerant generations amid ongoing digital disruptions, with broader implications for multicultural education and educational policy development.